2012
DOI: 10.1002/acr.21584
|View full text |Cite
|
Sign up to set email alerts
|

Toe‐out, lateral trunk lean, and pelvic obliquity during prolonged walking in patients with medial compartment knee osteoarthritis and healthy controls

Abstract: Objective. To compare the time-varying behavior of maximum toe-out angle, lateral trunk lean (over the stance leg), and pelvic obliquity (rise and drop on the swing leg) during prolonged walking in participants with and without medial compartment knee osteoarthritis (OA), and to explore correlations between these gait characteristics and pain. Methods. Twenty patients with knee OA and 20 healthy controls completed 30 minutes of treadmill walking. Toe-out, trunk lean, pelvic obliquity, and pain were measured at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Participants did not report any significant change in knee pain during increased lateral trunk lean walking when compared to normal walking. This is similar to the previous studies of lateral trunk lean walking in knee OA that also report an absence of acute symptomatic changes 12,14,16 . In particular, Simic et al 12 found no difference in pain between natural gait and increasing degrees of lateral trunk lean (6e12 attempted) in 22 individuals with knee OA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Participants did not report any significant change in knee pain during increased lateral trunk lean walking when compared to normal walking. This is similar to the previous studies of lateral trunk lean walking in knee OA that also report an absence of acute symptomatic changes 12,14,16 . In particular, Simic et al 12 found no difference in pain between natural gait and increasing degrees of lateral trunk lean (6e12 attempted) in 22 individuals with knee OA.…”
Section: Discussionsupporting
confidence: 91%
“…When asked to walk with a natural gait, our participants with knee OA walked with a trunk lean angle of 2.4 on average. It has been shown previously that individuals with knee OA often choose to adopt a trunk lean angle greater than zero 12,14,16,32 , with other studies 16 assessed natural lateral trunk lean during gait in 20 individuals with knee OA and found the mean amount of lateral trunk lean to be 2.0 . The 2.4 of lateral trunk lean seen in the current study when participants were asked to walk normally was considerably less than the 10 that participants were asked to target during the gait modification trials.…”
Section: Discussionmentioning
confidence: 85%
“…Finally, alterations in foot (toe-out) angle, are postulated to mediate medio-lateral knee forces and pain as suggested by Bechard et al. [28], Lynn and Costigan [29], and Simic et al. [30] and would alter shear forces both in the medio-lateral and antero-posterior directions.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased risk of OA in the older obese population, the high frequency of medial compartment involvement, and the fact that the adduction moment is a surrogate measure of medial‐lateral load distribution, this study also considers the factors that influence the adduction moment in obese individuals. It has previously been proposed that alterations in the placement of the lower limb during stance can affect the adduction moment by altering the length of the lever arm of the ground reaction force (GRF) . We therefore assess the mechanism of adduction moment change by considering alterations in the dynamic placement of the lower limb during walking, measured as the frontal plane distance between the knee and the midline of the body, as determined by the medial‐lateral center of the pelvis (relative knee–pelvis distance).…”
mentioning
confidence: 99%
“…The purpose of this study was to test the hypotheses that the adduction and flexion moments increase with age in healthy normal‐weight and obese individuals, and that changes in adduction moment are due to changes in lower limb position measured by the relative distance between the knee and pelvis centers (relative knee–pelvis distance). Static knee alignment, relative lower body volume distribution (% of total), GRF magnitude, toe‐out angle, and step width, which have been previously proposed as mechanisms that affect the magnitude of the adduction moment, were tested as covariates.…”
mentioning
confidence: 99%